2018
DOI: 10.1016/j.diamond.2018.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface composition on the colloidal stability of ultra-small detonation nanodiamonds in biological media

Abstract: Fluorescent nanodiamonds (NDs) are strong contenders as bio-labels for life science imaging, diagnostics and therapeutics. Ultimately, for their use in biomedical applications, their size should ideally be less than 10 nm. Yet, even more critical for their specificity and efficient uptake in cellular systems, is their resilience to aggregation, which is dictated by their colloidal stability in complex, physiological environments. To this end, we characterize ultrasmall detonation NDs (~5 nm) by examining their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) was performed using a Thermo Scientific Nicolet iS10 spectrometer to characterize the functional groups on the LMSY nanodiamond surface. ATR-FTIR showed an increase in the characteristic 1780 cm −1 carbonyl peak associated with carboxylic acid groups, confirming oxidation of the nanodiamond surface [51].…”
Section: A Sample Preparationmentioning
confidence: 85%
“…Attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) was performed using a Thermo Scientific Nicolet iS10 spectrometer to characterize the functional groups on the LMSY nanodiamond surface. ATR-FTIR showed an increase in the characteristic 1780 cm −1 carbonyl peak associated with carboxylic acid groups, confirming oxidation of the nanodiamond surface [51].…”
Section: A Sample Preparationmentioning
confidence: 85%
“…As a result, the negatively-charged DNDs showed good colloidal stability over a wide range of pH values, covering both, alkaline and acidic conditions, in comparison to BASD DNDs (positively-charged DNDs) as reported before. 47 Moreover, negatively-charged DNDs were shown to have a stronger aggregation resistance at higher ionic strength in comparison to positively-charged DNDs. 47 Finally, we observed that the freeze-dried air-oxidized DNDs after boiling acid were redispersed in water down to a singledigit size of 7.1 ± 0.3 nm (Figure 5(b)), sharing similar properties as SAUD DNDs, as well as horn sonication oxidized DNDs, but a remarkable difference to freeze-dried BASD DNDs, which cannot be redispersed in the same way and do show aggregation with two peaks of particle sizes 24.6 ± 2.6 nm and 619.4 ± 2.1 nm (Figure 5(b)).…”
Section: Colloidal Stability and Redispersibility Of Dnds: Madls And ...mentioning
confidence: 99%
“…These two approaches lead to hydroxylated and carboxylated NDs that are hydrophilic and have high dispersibility in aqueous solution, with typical zeta potentials of −30 to −50 mV and about +40 mV, respectively [ 21 ]. A recent publication on negatively charged NDs has shown that, compared to positively charged NDs of the same size, they are more resistant to aggregation and exhibit high colloidal stability in a wide range of pH values and salt concentrations [ 33 ]. Negatively charged NDs have a more homogeneous surface and their functional groups are mostly carboxy units.…”
Section: Synthesis Properties and Functionalisation Of Nanodiamondsmentioning
confidence: 99%